Intravitreal Bevacizumab for Treatment of Diabetic Macular Edema - Basum Mubaruk, Aurangzeb Khan, Aamir Ali Choudhry, Zahid Siddiq, Mahmood Hussain (Pakistan Journal of Ophthalmology, 2012)
Purpose: To evaluate the effects of Intra-vitreal Bevacizumab on visual function and macular edema in diabetic patients. Material and Methods: This study was conducted in the Department of Ophthalmology, Madina Teaching Hospital, University Medical and Dental College, Faisalabad. Three months from 1st June 2010 to 31st August 2010. A total of 26 eyes of 26 diabetic patients (mean age 48.92 years) with diabetic macular edema were included in this study. Best – corrected visual acuity, slitlamp biomicroscopic examination of anterior segment, fundus examination and fundus flourescein angiography, were done at baseline and at each follow up visits. All patients were treated with 0.05 ml intravitreal injection containing 1.25 mg of bevacizumab (IVB). Results: All patients completed 3 months follow up. The mean BCVA at baseline was 0.726 + log MAR. It improved to 0.515, 0.461, and 0.452 + log MAR at 1st week, 1st month, and 3rd months respectively. Final BCVA analysis demonstrated that 17 (65.38%) patients improved ? 2 lines of Senellen’s visual acuity chart, 7 (26.38%) improved by one line, one (3.84%) remained stable, and one (3.84%) showed deterioration of one line. Macular edema at 1st week resolved completely in 18 (69.23%) and moderately in 7 (26.92%) patients at 1st month and 3rd month follow up resolved moderately in 24 (92.30%). Flourecein leakage stopped in 25 (96.15%) patients. No ocular toxicity or adverse effects to drug were observed. Conclusions: IVB injection resulted in improvement of visual acuity, resolution of macular edema and stoppage of Flourescein leakage as early as 1st week after injection in patients with DME. The slight reduction in visual improvement at 3rd months suggests wearing of effect of drug. Further clinical trials will be needed to evaluate the long term safety and efficacy of this drug.